Status and perspectives of biomarker validation for diagnosis, stratification, and treatment. (January 2021) - Skov, J.; Kristiansen, K.; Jespersen, J.; Olesen, P.
Abstract: Objectives: The aim of this study was to discuss the status of and perspective for biomarker validation in view of the challenges imposed on national healthcare systems due to an increasing number of citizens with chronic diseases and new expensive drugs with effects that are sometimes poorly documented. The demand for a paradigm shift toward stratification of patients or even 'personalized medicine' (PM) is rising, and the implementation of such novel strategies has the potential to increase patient outcomes and cost efficiency of treatments. The implementation of PM depends on relevant and reliable biomarkers correlated to disease states, prognosis, or effect of treatment. Beyond biomarkers of disease, personalized prevention strategies (such as individualized nutrition guidance) are likely to depend on novel biomarkers. Study design: We discuss the current status of the use of biomarkers and the need for standardization and integration of biomarkers based on multi-omics approaches. Methods: We present representative cases from laboratory medicine, oncology, and nutrition, where present and emerging biomarkers have or may present opportunities for PM or prevention. Results: Biomarkers vary greatly in complexity, from single genomic mutations to metagenomic analyses of the composition of the gut microbiota and comprehensive analyses of metabolites, metabolomics. Using biomarkers for decision-making has previously often relied on measurements of single biomolecules. The current development now moves toward the use of multiple biomarkers requiring the use of machine learning or artificial intelligence. Still, the usefulness of biomarkers is often challenged by suboptimal validation, and the discovery of new biomarkers moves much faster than standardization efforts. To reap the potential benefits of personalization of treatment and prevention, healthcare systems and regulatory authorities need to focus on validation and standardization of biomarkers. Conclusion: There is a great public health need for better understanding of the usefulness, but also limitations, of biomarkers among policy makers, clinicians, and scientists, and efforts securing effective validation are key to the future use of novel sets of complex biomarkers. Highlights: Single biomarkers have been studied and described in many different fields. Biomarkers can be combined based on the data obtained by multiple omics technologies. There is a great public health need for better understanding of biomarkers.